1973
DOI: 10.1007/bf00891646
|View full text |Cite
|
Sign up to set email alerts
|

A systems analysis of a campus community mental health facility: A preliminary investigation

Abstract: Faced with increasing demand and relatively static resources, community mental health facilities need to evaluate their functions in terms of time, cost, and performance effectiveness. For this study, the technology of systems analysis was applied to the functions of a progressive university counseling center. The systems analysis provided a management and information flow analysis and a time and cost analysis, as well as a performance analysis. This study focused on the preliminary results of the time, cost, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1976
1976
1976
1976

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…An example of process evaluation research that incorporates some of Kelly's recommendations was recently reported by O'Neil et al (1973). These authors used a systems analysis methodology to evaluate the effectiveness of the organizational structure and staff functions of the Counseling Center at the University of Texas at Austin.…”
Section: Process Evaluation: a Systems Analysis Of A Campus Communitymentioning
confidence: 99%
See 4 more Smart Citations
“…An example of process evaluation research that incorporates some of Kelly's recommendations was recently reported by O'Neil et al (1973). These authors used a systems analysis methodology to evaluate the effectiveness of the organizational structure and staff functions of the Counseling Center at the University of Texas at Austin.…”
Section: Process Evaluation: a Systems Analysis Of A Campus Communitymentioning
confidence: 99%
“…Nonsalary costs were estimated by apportioning overhead on the basis of a complex formula that is beyond the scope of this paper (O'Neil et al, 1973). Program cost allocations were made on the basis of the percentage of "total client hours" generated by the program.…”
Section: Process Evaluation: a Systems Analysis Of A Campus Communitymentioning
confidence: 99%
See 3 more Smart Citations